(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2024)
The main aim of the article was to assess the diversity of hotel services in the context of tourism regionalization in Poland. Therefore, a comparative analysis was carried out in addition to a SWOT analysis. The article compares four offers from four different regions of Poland. The offer referring to the Kashubian culture (Pomeranian Voivodship), the rustic offer (Warmińsko-Mazurskie Voivodship), the offer based on elements of highlander culture (Małopolskie Voivodeship) and the offer related to the nature and culture of Lower Silesia (Lower Silesian Voivodship) were analysed. Based on the conducted research, research hypotheses were confirmed, according to which tourism regionalization in Poland determines the diversity of hotel services, as well as regional tourist values are an integral element of the hotel offer in Poland.